Aspek Hukum Atas Standardisasi Pada Produk Pangan Hasil Rekayasa Genetika - Hernawati, Elly (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
Standardization is a process that can be used as a reference to maintain the qualifications and specifications of a product, so as to improve quality, efficiency in production and facilitate trade transactions and create healthy competition among business actors. In the era of globalization, the determination of Standardization needs to be carried out in various fields of life, considering that without a certain standard it can lead to various problems. The laws and regulations regarding Standardization aim to provide legal protection to producers, consumers, and the public from various aspects, for example related to security, safety, health and the preservation of environmental functions, with the hope that this will encourage increased competitiveness for products. circulating in this era of globalization. Advances in technology will affect the industrial world, especially the food industry, one of which is the emergence of a variety of food products circulating in the community, both those produced in Indonesia, and imported products. In addition, it does not rule out the possibility of developments in food technology with the aim of improving the quality, quality, and benefits of the use of these food products. The results of food technology being developed today are genetically engineered food products. Indonesia is one of the countries that has biodiversity, and through a certain technology the utilization of this biodiversity will produce genetically engineered products. The use of the results of this technology can lead to benefits as well as risks to human health if standardization is not complied with as specified in the applicable laws and regulations.